2019
DOI: 10.3390/ma12071042
|View full text |Cite
|
Sign up to set email alerts
|

Stress Intensity Factor of Semielliptical Surface Crack in Internally Pressurized Hollow Cylinder—A Comparison between BS 7910 and API 579/ASME FFS-1 Solutions

Abstract: The purpose of this research is to compare both British standard BS 7910 (2013) and American standard API 579/ASME FFS-1 (2016) stress intensity factor (SIF) solutions by considering a series of semielliptical surface cracks located in the external surface of a pressurized hollow cylinder in the axial direction. Finite element analysis was used as a comparison basis for both standards’ SIF results. The solution from the British standard provided consistent results compared to Finite Element (FE) results for cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…As shown in Appendix A. Likewise, as shown in Appendix A.3, Coelho et al [39] compared their FEA results of stress intensity factors for a wide range of surface crack sizes (0.25 < a/t < 0.8) with API 579 and BS 7910 estimates. They obtained the same conclusions made by Tiku et al [52], that is, 1) API 579 tabular data agree with the FEA results for all crack sizes, and 2) BS 7910 overestimates the FEA results for deep cracks with a/t > 0.5.…”
Section: Comparison Of Stress Intensity Factor Solutions For Surface ...mentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Appendix A. Likewise, as shown in Appendix A.3, Coelho et al [39] compared their FEA results of stress intensity factors for a wide range of surface crack sizes (0.25 < a/t < 0.8) with API 579 and BS 7910 estimates. They obtained the same conclusions made by Tiku et al [52], that is, 1) API 579 tabular data agree with the FEA results for all crack sizes, and 2) BS 7910 overestimates the FEA results for deep cracks with a/t > 0.5.…”
Section: Comparison Of Stress Intensity Factor Solutions For Surface ...mentioning
confidence: 99%
“…Recently, Coelho et al [39] performed 3D FEA calculations of stress intensity factors for axial outside surface cracks in a pressurized cylinder made of a structural steel using four FEA models with a mesh size h=12 mm, 10 mm, 8 mm, or 6 mm. The cylinder has an inside radius of 1139.75 mm (44.87 in.)…”
Section: A3 Comparison Of Api 579 and Bs 7910 Stress Intensity Factor...mentioning
confidence: 99%
See 1 more Smart Citation
“…Delliou and Chapuliot [12] compared the tabular data of K in API 579 with those used in French pressure vessel code RSE-M, and showed that the K solutions in both standards agree satisfactorily. Ceelho et al [13] performed the case study of surface cracks in cylinders using the advanced 3D FEA simulations, and showed that the tabular data of K in API 579 are generally accurate and adequate to use for the FFS evaluation of pressure vessels. Recently, Li and Hasegawa [14,15] further obtained the FEA results of K for surface cracks in cylinders with high aspect ratios that are not considered in API 579.…”
Section: Introductionmentioning
confidence: 99%
“…Elamvazhudi and Gopalakannan 16 carried out fatigue growth of a semielliptical crack on the outer surface of a butt‐welded joint using FEM. El Fakkoussi et al 17 and Coêlho et al 18 computed the SIF for an external longitudinal semielliptic crack in a cylinder using FEM. Shim et al 19 and Zareei and Nabavi 20,21 extracted a weight function (WF) for internal semielliptical circumferential cracks to determine SIFs for various loading states, including residual welding stress.…”
Section: Introductionmentioning
confidence: 99%